Digital Community Engagement : Partnering Communities with the Academy - Schadewald, Paul; Heppler, Jason A.; Wingo, Rebecca S. (Book collections on Project MUSE., 2020)
"Digital Community Engagement: Partnering Communities with the Academy brings together cutting-edge campus- community partnerships with a focus on digital projects and technology to co-create histories in digital environments. This is the first book of its kind to bring together scholars and community partners to, in collaboration with each other, discuss, often in their own voices, community-engaged digital projects. Through a series of case studies authored by these teams, this edited volume explores models for cross-disciplinary digital community engagement that leverages new media through reciprocal partnerships. The contributions to the volume stand at the crossroads of digital humanities, public history, and community engagement, drawing ideas, methods, and practices from various disciplines to inform our public partnerships. The contributors "lift the hood" on their projects, so to speak, by detailing what made each project successful and meaningful. They also describe how the digital components changed their approaches and outcomes. By highlighting these projects, the authors provide other institutions with roadmaps and ideas for cultural heritage organizations, universities, and communities' models of successful engagement and tips on how to navigate the fragile relationships between communities and the academy"--